Training in intraoperative handover and display of a checklist improve communication during transfer of care: An interventional cohort study of anaesthesia residents and nurse anaesthetists. Issue 7 (July 2017) - Jullia, Marion; Tronet, Anaïs; Fraumar, Fabiola; Minville, Vincent; Fourcade, Olivier; Alacoque, Xavier; LeManach, Yannick; Kurrek, Matt M.
Abstract : BACKGROUND: Handovers during anaesthesia are common, and failures in communication may lead to morbidity and mortality. OBJECTIVES: We hypothesised that intraoperative handover training and display of a checklist would improve communication during anaesthesia care transition in the operating room. DESIGN: Interventional cohort study. SETTING: Single-centre tertiary care university hospital. PARTICIPANTS: A total of 204 random observations of handovers between anaesthesia providers (residents and nurse anaesthetists) over a 6-month period in 2016. INTERVENTION: Two geographically different hospital sites were studied simultaneously (same observations, but no training/checklist at the control site): first a 2-week 'baseline' observation period; then handover training and display of checklists in each operating room (at the intervention site only) followed by an 'immediate' second and finally a third (3 months later) observation period. MAIN OUTCOME MEASURES: A 22-item checklist was created by a modified DELPHI method and a checklist score calculated for each handover by adding the individual scores for each item as follows: −1, if error in communicating item; 0, unreported item; 0.5, if partly communicated item; 1, if correctly communicated item. RESULTS: Before training and display of the checklist, the scores in the interventional and the control groups were similar. There was no improvement in the control group's scores over the three observation periods. In the interventional group, the mean (95% confidence interval) score increased by 43% [baseline 7.6 (6.7 to 8.4) n = 42; 'immediate' 10.9 (9.4 to 12.4) n = 27, P < 0.001]. This improvement persisted at 3 months without an increase in the mean duration of handovers. CONCLUSION: Intraoperative handover training and display of a checklist in the operating room improved the checklist score for intraoperative transfer of care in anaesthesia.